Profiles of compounds in root exudates of rice, cymbopogon, desmodium, mucuna and maize - Kaiira Moses G.; Chemining'wa George N.; Ayuke Fredrick; Baguma Yona; Nganga Fredrick (Journal of Agricultural Sciences (Belgrade), 2019)
Roots of crop species produce exudates with biologically active chemicals which are known to affect the growth of crops and weed species. An experiment was conducted at the Uganda National Crop Resources Research Institute, Namulonge during 2016 to identify compounds released in root exudates of potted Cymbopogon nardus, Desmodium uncinatum, upland rice (NERICA 1), Mucuna pruriens and Zea mays (LONGE 6H) at forty-five days after planting. This marked near the average stationary phase for test crop growth when secondary metabolite levels were high. Organic compounds in soils were extracted using solid-phase micro-extraction (SPME) and by solvent extraction. Samples were subjected to analysis using a 7890A Gas Chromatography system. Data files were transferred into a distinct folder and data was uploaded onto the XCMS online platform for pairwise comparison and other related statistical analyses in the National Institute of Science and Technology Library. The blank soil produced 15 terpenoids, two alcohols and one each of trihalomethanes, ethers, phenols, ketones, furans, alkanes and aldehydes. Cymbopogon exuded five terpenoids, one phenol and an alkane. Desmodium plant roots released three terpenoids, one alkane and a phenol. The rice crop produced eight terpenoids, two alkanes and a furan. Five terpenoids, one phenol and an alkane were released by the mucuna crop, while six terpenoids were found in maize soil. The profiled compounds from cymbopogon, desmodium, rice, mucuna and maize could be responsible for allelopathic properties expressed by the study crops in natural and agricultural ecosystems and could be used in synthesis and development of herbicides.